2016
DOI: 10.7326/m15-2762
|View full text |Cite
|
Sign up to set email alerts
|

Familial Clustering ofStaphylococcus aureusBacteremia in First-Degree Relatives

Abstract: The Danish Heart Foundation and the Christian Larsen and Judge Ellen Larsen Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…12, 13 Although a twin study failed to demonstrate an association between nasal carriage of monozygotic twin status, 30 a recent 20-year nationwide cohort study drawing from the entire Danish population of >8 million individuals showed evidence of familial clustering of SAB in first-degree relatives. 6 Among the 34 774 individuals with a first-degree relative (index case patient) previously hospitalized with SAB who were followed for a mean of 7.8 years, a higher rate of SAB was observed among first-degree relatives than among the background Danish population (standardized incidence ratio (SIR): 2.49; (95% confidence interval (CI): 1.95–3.19)). This estimate was significantly higher if the index case patient was a sibling (SIR: 5.01; (95% CI: 3.30–7.62) than a parent and highest in siblings of individuals who developed non-hospital acquired SAB (SIR: 5.66; (95% CI: 3.47–9.24)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12, 13 Although a twin study failed to demonstrate an association between nasal carriage of monozygotic twin status, 30 a recent 20-year nationwide cohort study drawing from the entire Danish population of >8 million individuals showed evidence of familial clustering of SAB in first-degree relatives. 6 Among the 34 774 individuals with a first-degree relative (index case patient) previously hospitalized with SAB who were followed for a mean of 7.8 years, a higher rate of SAB was observed among first-degree relatives than among the background Danish population (standardized incidence ratio (SIR): 2.49; (95% confidence interval (CI): 1.95–3.19)). This estimate was significantly higher if the index case patient was a sibling (SIR: 5.01; (95% CI: 3.30–7.62) than a parent and highest in siblings of individuals who developed non-hospital acquired SAB (SIR: 5.66; (95% CI: 3.47–9.24)).…”
Section: Discussionmentioning
confidence: 99%
“…5 In humans, first-degree relatives of patients previously hospitalized with S. aureus bacteremia (SAB) were themselves significantly more likely to develop SAB than the population as a whole. 6 Our recent genome-wide study of >50 000 white subjects found that two single-nucleotide polymorphisms (SNPs) in the human leukocyte antigen (HLA) class II region on chromosome 6 were associated with susceptibility to S. aureus infection at a genome-wide significant level. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Transition from carriage to bloodstream infection and further on to IE may thus rather be due to host genetics and host immune responses than caused by specific traits of the infecting bacterium. In support of this, we have recently reported a higher incidence of S. aureus bacteraemia among first degree relatives of S. aureus patients compared to the general population, suggesting that there is a host genetic component, partly explaining why some individuals are more prone to acquire S. aureus bacteraemia than others [ 44 ]. Specific host gene variants have also been associated to susceptibility to endocarditis [ 45–48 ].…”
Section: Discussionmentioning
confidence: 86%
“…A growing body of evidence suggests that human genetic variability may influence the risk for and severity of S. aureus infections, including complicated SAB and IE. Evidence supporting a genetic basis for susceptibility to SAB includes: i) higher rates of S. aureus infections in distinct ethnic populations (5256); ii) familial clusters of S. aureus infection (5760); iii) rare genetic conditions causing susceptibility to S. aureus (6166); and iv) variable susceptibility to S. aureus in inbred mice (6771) and cattle (72,73). The first GWAS evidence of human genetic susceptibility to S. aureus infection by comparing 4,701 cases of S. aureus infection and 45,344 matched controls was presented (74).…”
Section: Discussionmentioning
confidence: 99%